Pengaruh Pendidikan Kesehatan Tentang Pernikahan Dini Terhadap Tingkat Pengetahuan Dan Sikap Remaja Kelas XII di SMA Budi Insani Kel. Kwala Bekala Kec. Medan Johor Kota Medan - Kamelia Sinaga (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
According to the World Health Organization (WHO), the adolescent population is a fairly large group of people aged 10-19 years, with a figure of almost 43 million people (18.3%) of the total population. Adolescence is a period of growth and development both physically, psychologically and intellectually. Teenagers tend to have great curiosity, like challenges and dare to take risks in their actions. This type of research is quasi-experimental in nature using a One Group Pretest-Posttest Design. The type of sampling that will be taken in this research is the Total Sampling Method. The sample in this study was Class XII SMA Budi Insani Kel. Kwala Bekala District. Medan Johor, Medan City, there were 30 respondents. Based on the results obtained, it shows that the average knowledge of students before being given health education is 1.40, while after being given health education is 2.66. The statistical test results obtained a significant value with P Value (0.000) < a (0.05) so that Ho was rejected. Meanwhile, data obtained from student attitude data shows that the average student attitude before being given health education was 1.46 while after being given health education was 2.63. Based on the results of statistical tests using the Wilxocon test, the p value of knowledge = 0.000 <0.05 and the p value of attitude = 0.000 <0.05. So it is proven that there is a significant influence between health education about early marriage on the level of knowledge and attitudes of class XII students at SMA Budi Insani Kel. Kwala Bekala District. Medan Johor Medan City